2013
DOI: 10.1371/journal.pone.0066070
|View full text |Cite
|
Sign up to set email alerts
|

The Proto-Oncogene TWIST1 Is Regulated by MicroRNAs

Abstract: Upregulation of the proto-oncogene Twist1 is highly correlated with acquired drug resistance and poor prognosis in human cancers. Altered expression of this multifunctional transcription factor is also associated with inherited skeletal malformations. The mammalian Twist1 3′UTRs are highly conserved and contain a number of potential regulatory elements including miRNA target sites. We analyzed the translational regulation of TWIST1 using luciferase reporter assays in a variety of cell lines. Among several miRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…Control of BCL2 expression via miR-24-2 (strongly upregulated in both proximal and distal tumors), has been previously reported in human embryonic kidney and breast cancer cell lines [47]. Interestingly, several uniquely regulated miRs correlate significantly with (hypermethylated) TWIST1, a primal transcription factor uniquely upregulated within proximal tumors [48], whose activation has been implicated in reverting cells to a non-lineage specific proliferative state. Only two miRs however, are uniquely regulated within distal tumors-miR-3607 and miR-29a (Fig.…”
Section: Rscc Exhibits Pronounced Post-transcriptional Regulationmentioning
confidence: 65%
“…Control of BCL2 expression via miR-24-2 (strongly upregulated in both proximal and distal tumors), has been previously reported in human embryonic kidney and breast cancer cell lines [47]. Interestingly, several uniquely regulated miRs correlate significantly with (hypermethylated) TWIST1, a primal transcription factor uniquely upregulated within proximal tumors [48], whose activation has been implicated in reverting cells to a non-lineage specific proliferative state. Only two miRs however, are uniquely regulated within distal tumors-miR-3607 and miR-29a (Fig.…”
Section: Rscc Exhibits Pronounced Post-transcriptional Regulationmentioning
confidence: 65%
“…It was also found that miR-151-3p represses the full-length isoform of human neurotrophin-3 receptor gene NTRK3 in neuroblastoma cells [37]. It was recently demonstrated that miR-151-5p and a combination of other miRNAs (miR-145a-5p or miR-337-3p) are able to significantly repress TWIST1translation and result in decreased migratory potential of murine embryonic fibroblast cells [19]. In the role of miR-151-3p in muscle fiber type determination, miR-151-3p was shown to directly target ATP2a2, a gene that encodes for a slow skeletal and cardiac muscle specific Ca 2+ ATPase known as SERCA2, thus downregulating slow muscle gene expression [38].…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, miR-151-5p expression levels were not different among tumors of varying grades, but the level was significantly lower in the lymph-node metastases than in their corresponding tumors of breast cancer patients [18]. It was recently demonstrated that miR-151-5p combined with other miRNAs (miR-145a-5p or miR-337-3p) are able to significantly repress TWIST1 translation and result in the decreased migratory potential of murine embryonic fibroblast cells [19]. However, the role of miR-151 in breast cancer progression and its direct targets in the regulation of breast cancer metastasis are still undefined.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, differences in the mRNA levels of these DNA trans-factors were not observed in these NGS data. Because CPEB2 has been implicated as a translational repressor of TWIST1 and HIF1␣ (10,11), our findings coupled to these published reports formed the premise that CPEB2A is the suppressing form of CPEB2 on TWIST1 protein expression as reported by others (9,10), whereas CPEB2B has the previously unexplored function of activating the expression of these DNA trans-factors in response to cellular stress or the acquisition of AnR. In line with this premise, we observed that both HIF1␣ and TWIST1 were up-regulated in AnR MDA-MB-231 cells, which correlated with a decrease in the CPEB2A/ CPEB2B ratio ( Fig.…”
Section: Cpeb2 Rna Splicing Regulates Emt and Hypoxic Responsesmentioning
confidence: 99%